From Bits to Bodies: Perfect Humans, Bioinformatic Visualizations, and Critical Relationality - Hamilton, Jennifer A (Imaginations: Journal of Cross-Cultural Image Studies, 2019)
<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;">In December 2014, computational biologist Lior Pachter posted the results of his “tongue in cheek” <em style="box-sizing: border-box; font-style: italic; caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">in silico<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;"> genome experiment on his personal blog, where he declared his discovery that “the perfect human is Puerto Rican.” In this article, I analyze the “perfect human” experiment. I argue that despite the use of 21<sup style="box-sizing: border-box; font-size: 10.5px; line-height: 0; vertical-align: baseline; position: relative; top: -0.5em; caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">st<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;">-century, cutting-edge technology in computing and genomics, Pachter’s experiment and his use of visualization can be usefully juxtaposed with earlier modes of <em style="box-sizing: border-box; font-style: italic; caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">visualizing heredity<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;">, namely the development of composite portraiture in the late-19<sup style="box-sizing: border-box; font-size: 10.5px; line-height: 0; vertical-align: baseline; position: relative; top: -0.5em; caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">th<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;"> century and late-20<sup style="box-sizing: border-box; font-size: 10.5px; line-height: 0; vertical-align: baseline; position: relative; top: -0.5em; caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">th<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;"> century technologies of “morphing.” I temper the celebration of Pachter’s creation of a “mixed race” perfect human <em style="box-sizing: border-box; font-style: italic; caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none;">in silico<span style="caret-color: #484848; color: #484848; font-family: Karla, sans-serif; font-size: 14.000000953674316px; font-style: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px; text-decoration: none; display: inline !important; float: none;"> with a challenge to its ostensibly progressive stance. I instead suggest that it must be understood in the broader context of eugenic hauntings and contemporary tensions around questions of sex, sexuality, race, nation, and indigeneity. I argue that the scientific, specifically genomic, stories that we tell, can be productively read in light of critiques of biogenetic kinship and the naturalization of heterosexual love. I conclude by arguing that the perfect human experiment makes a particular kind of argument about what it means to be human and perfect and what constitutes legitimate and cognizable modes of relationality.